Islamic Education 4.0: Rethinking Moral and Religious Learning for a Socially Conscious Generation - velly, Velly; Rahman, Arif; Alharbi, Abeer; Awan, Naila (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
Abstract Islamic Education 4.0 represents a critical response to the challenges and opportunities brought by the Fourth Industrial Revolution. This study fills a research gap in the comparative analysis of Islamic education systems by examining how Indonesia, Malaysia, and Saudi Arabia integrate digital technology within their educational systems. Using the Systematic Literature Review (SLR) method and a descriptive qualitative approach, this study analyzes 63 scholarly sources published between 2019 and 2025. The results indicate that Malaysia is making progress with structured digital policies and student-centered pedagogy, while Saudi Arabia is leading in artificial intelligence (AI) integration through its Vision 2030 initiative; in contrast, Indonesia continues to face challenges related to infrastructure, digital literacy, and policy implementation. This study suggests a step-by-step plan to improve Islamic education in Indonesia by focusing on building ethical digital skills, updating teaching methods, and preparing institutions better. The study contributes to the discourse on Islamic Education 4.0 by providing a contextual strategic guide to harmonize technological adaptation with Islamic ethical values in today’s digital era. Abstrak Pendidikan Islam 4.0 merupakan respons kritis terhadap tantangan dan peluang yang dibawa oleh Revolusi Industri Keempat. Studi ini mengisi kesenjangan penelitian dalam analisis komparatif sistem pendidikan Islam dengan mengkaji bagaimana Indonesia, Malaysia, dan Arab Saudi mengintegrasikan teknologi digital dalam sistem pendidikan mereka. Dengan menggunakan metode Systematic Literature Review (SLR) dan pendekatan kualitatif deskriptif, studi ini menganalisis 63 sumber ilmiah yang diterbitkan antara tahun 2019 hingga 2025. Hasil penelitian menunjukkan bahwa Malaysia mengalami kemajuan melalui kebijakan digital yang terstruktur dan pendekatan pedagogi yang berpusat pada siswa, sementara Arab Saudi memimpin dalam integrasi kecerdasan buatan (AI) melalui inisiatif Vision 2030. Sebaliknya, Indonesia masih menghadapi tantangan yang berkaitan dengan infrastruktur, literasi digital, dan implementasi kebijakan. Studi ini mengusulkan rencana bertahap untuk meningkatkan pendidikan Islam di Indonesia dengan menekankan pada pembangunan keterampilan digital yang etis, pembaruan metode pengajaran, dan peningkatan kesiapan institusi. Studi ini berkontribusi pada wacana Pendidikan Islam 4.0 dengan menyediakan panduan strategis kontekstual untuk menyelaraskan adaptasi teknologi dengan nilai-nilai etika Islam di era digital saat ini.